Incidence of hip fracture in Kermanshah, Iran - Beyranvand, Mandana (Springer-Verlag, 2009)
SUMMARY: The aim of this study was to estimate the incidence of hip fracture in Kermanshah, Iran. 161 cases (88 men and 73 women) were recorded. The annual age-standardized incidence rates were 181.1/100,000 in men and 214.6/100,000 in women. Incidence rate of hip fracture was less than in Western countries. INTRODUCTION: Hip fracture is the most serious complication of osteoporosis, the most common metabolic bone disease worldwide. The incidence of hip fracture in the elderly patients varies in different areas. The aim of this study was to estimate the incidence rate of hip fracture in Kermanshah, Iran. MATERIALS AND METHODS: All cases of hip fracture patients who aged 50 years or more admitted in six referral orthopedic hospitals in Kermanshah from May 21, 2007 to May 21, 2008 were studied. The age- and sex-specific incidence rates of hip fracture per 100,000 persons were calculated using the population data from the last national census in Iran, 2007. RESULTS: A total of 161 cases of hip fracture (88 men and 73 women) were recorded. The annual age-standardized incidence rates were 181.1/100,000 in men and 214.6/100,000 in women. The female to male ratio of hip fracture incidence was 1.18. CONCLUSION: We found a relatively low incidence of hip fracture in Iran than in Western countries, which is mostly due to the lower rate in women. This is probably related to the different lifestyle factors in different societies.